KUALITAS PELAYANAN TERHADAP NIAT MENGUNJUNGI KEMBALI PADA BENGKEL MOTOR UMUM DI SURAKARTA - Rusnandari Retno Cahyani (Universitas Sahid Surakarta, 2016)
Competition is getting tougher going on in the automotive industry, especially motorcycle product because this product is a tool of the most dominant land transport and required a lot owned by the public. Thus, making the motorcycle repair business is one of the most sought after business services. a general motor-cycle repair workshop private property or individuals who offer service, spare parts replacement, and maintenance to the motor with a common brand. Quantitative research with the consumer population bike shop in Surakarta. The results showed that service quality in business services and significant positive effect on the inter-est revisited at the general bike workshop with case studies in Surakarta.